The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/prot.22177
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics guided study of salt bridge length dependence in both fluorinated and non‐fluorinated parallel dimeric coiled‐coils

Abstract: The α-helical coiled-coil is one of the most common oligomerization motifs found in both native and engineered proteins. To better understand the stability and dynamics of coiled-coil motifs, including those modified by fluorination, several fluorinated and non-fluorinated parallel dimeric coiled-coil protein structures were designed and modeled. We also attempt to investigate how changing the length and geometry of the important stabilizing salt bridges influences the coiledcoil protein structure. Molecular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 172 publications
6
17
0
Order By: Relevance
“…Pendley et al recently presented a theoretical study of a highly fluorinated parallel coiled-coil heterodimer that contained 5 3 ,5 03 -F 6 Leu at all d-positions of both monomers. 45 Their simulations confirm the experimental findings that fluorination of Leu increases stability of the helical interactions thereby enhancing coiled-coil formation. Interestingly, their studies suggest that the dimer is not only stabilized by the increased hydrophobicity of the fluorinated side chain.…”
Section: Helical Structuressupporting
confidence: 61%
“…Pendley et al recently presented a theoretical study of a highly fluorinated parallel coiled-coil heterodimer that contained 5 3 ,5 03 -F 6 Leu at all d-positions of both monomers. 45 Their simulations confirm the experimental findings that fluorination of Leu increases stability of the helical interactions thereby enhancing coiled-coil formation. Interestingly, their studies suggest that the dimer is not only stabilized by the increased hydrophobicity of the fluorinated side chain.…”
Section: Helical Structuressupporting
confidence: 61%
“…We found that a single substitution of Leu with 5 3 ,5' 3 -F 6 Leu leads to a slight increase in helicity and an increase in thermal stability, which can be explained by the highly favorable burial of the bulky hydrophobic fluorinated side chain. Thus, our experimental findings confirm the results of a theoretical study by Pendley et al, who found a free energy of hydration lower by 1.1 kcal mol -1 for 5 3 ,5' 3 -F 6 Leu compared to leucine [29]. The evaluation of high resolution X-ray structures of other peptides and proteins containing 5 3 ,5' 3 -F 6 Leu residues have shown that, although larger, these fluorinated residues preserve the shape of the A c c e p t e d M a n u s c r i p t 9 hydrophobic side chains that they substitute and thus are well accommodated within the coiled coil hydrophobic core with only minimal structural perturbations [7].…”
Section: Resultssupporting
confidence: 95%
“…F 6 Leu is similar to Aha in hydrophobicity, while exhibiting a much larger volume. In a free energy perturbation study, the hydration energy of F 6 Leu was shown to be 1.1 kcal/mol higher than that of leucine [29]. This, together with our previous and new findings, suggests that there are two factors determining the overall hydrophobicity of fluorinated amino acids [26].…”
Section: Resultsmentioning
confidence: 76%